Finerenone Alleviates Over-Activation of Complement C5a-C5aR1 Axis of Macrophages by Regulating G Protein Subunit Alpha i2 to Improve Diabetic Nephropathy - Zi-Han Li; Zi-Jun Sun; Sydney C. W. Tang; Ming-Hui Zhao; Min Chen; Dong-Yuan Chang (Cells)
Diabetic nephropathy (DN), one of the most common complications of diabetes mellitus (DM), accounts for a major cause of chronic kidney disease (CKD) worldwide, with a complicated pathogenesis and limited effective strategies nowadays. The mineralocorticoid receptor (MR) is a classical ligand-activated nuclear transcription factor. It is expressed in the renal intrinsic and immune cells, especially macrophages. Over-activation of the MR was observed in patients with DN and was associated with DN prognosis. The renoprotective role of a new generation of non-steroidal selective mineralocorticoid receptor antagonist (MRA), finerenone, has been confirmed in DM and CKD patients. However, the mechanism by which finerenone improves renal inflammation in DN has yet to be completely understood. It was found in this research that the oral administration of finerenone attenuated the kidney injuries in established DN in db/db mice, and particularly improved the pathological changes in the renal tubulointerstitia. Specifically, finerenone inhibited the over-activation of the MR in macrophages, thereby reducing the expression of G protein subunit alpha i2 (GNAI2, Gnαi2), a key downstream component of the C5aR1 pathway. Animal experiments demonstrated that C5aR1 knockout alleviated renal injuries, confirming the critical pathogenic role of C5aR1 in DN. Moreover, finerenone mitigated inflammatory and chemotaxis responses by downregulating Gnαi2 in macrophages. These effects were reflected by reduced expressions of the pro-inflammatory chemokines CXCL15 and CCL2, the regulation of macrophage polarization and improvements in apoptosis. This study intends to understand the protective role of finerenone in DN, which is conducive to revealing the pathophysiological mechanism of DN and further optimizing the treatment of DN patients.